KNOWLEDGE, ATTITUDES AND PRACTICES OF TYPE 2 DIABETIC PATIENTS - Gul, Naheed (Journal of Ayub Medical College Abbottabad, 2010)
Background: Education is the cornerstone of diabetes care. Because of lack of awareness, most patients suffer from diabetes complications. This study was conducted to determine the knowledge, attitudes and practices among patients with type 2 diabetes. Methods: This descriptive study included one hundred type 2 diabetics. Patients were interviewed using a structured questionnaire. The mean age of the patients was 50±5 years with the male to female ratio being 1:3. The data was collected using convenience sampling technique and analyzed using statistical package Epi Info 6.0. The patients, knowledge about the disease, their attitudes and practices were the main outcome measures. Results: In our study, patients' awareness about diabetes was low. The mean of correct answers for glycemic control, risk factors and complications was 33.5%, 69% and 39% respectively. Sixty-one percent of the patients regularly checked blood sugar but only few knew target blood glucose values. Only one sixth of all the patients could correctly answer question regarding nutrition. 92% recognized blood pressure as a risk factor while the correct answers for hyperlipedimia, cigarette smoking, sedentary life style and body weight were 42%, 70%, 76% and 66% respectively. Awareness about eye and renal complications was also quite low. Doctors were the main source of information available to the test population. Conclusions: The knowledge, attitude and practice scores were low in most areas of diabetes care emphasising the need for additional educational efforts. Keywords: Type 2 diabetes, knowledge, attitudes, practices